Penulisan Soal Literasi Numerasi bagi Guru SD di Kabupaten Ponorogo - Shofan Fiangga; Siti M. Amin; Siti Khabibah; Rooselyna Ekawati; Nina Rinda Prihartiwi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2019)
The change in curriculum aims to improve the quality of content and learning. One of the backgrounds of the curriculum revision is based on international tests on students’ competency and literation, such as PISA. In PISA, literacy-numeracy becomes one of the essential evaluation of mathematics competency. Therefore, the use of literacy problems should be administered in the primary school class. In order to implement the literacy-numeracy problem in the class well, the teachers are required to be able to develop functional literacy problems. This workshop on writing literacy-numeracy for elementary teachers in Ponorogo City was conducted in three stages. The first stage collected the fundamental knowledge of the teachers about what they understand about literacy-numeracy. The second stage was a discussion about the literacy-numeracy and its both background and classroom implementation, especially in elementary school. The last stage was the teachers’ workshop in arranging the literacy-numeracy problems. In the end, the problems developed by the teachers were analyzed based on literacy-numeracy criteria. Besides, the participants also gave feedback using a questionnaire as the information for the effectivity of the workshop.